Integration of Information and Communication Technology in Teaching Reading: A Case Study of Vocational School in Tanjungpinang - Defitri, Aldanika; Erwin Pohan; Rona Elfiza (CV. Kalimasada Group Profesional, 2025)
The integration of Information and Communication Technology (ICT) enhanced teaching and learning, particularly in reading, by making lessons interactive and resource-rich. While ICT integration in teaching English skills had been widely discussed, its specific impact on teaching reading remained underexplored. This study investigated the ICT tools integrated by an English teacher at SMKN 1 Tanjungpinang and the impact on teaching reading. Employing a qualitative embedded case study design, data were collected through interview, observation, and document analysis involving one teacher and 15 students from a vocational school in Tanjungpinang. The findings revealed that laptop, projector, speaker, and applications like Kahoot! and PowerPoint were commonly used ICT tools. The integration of ICT increased student engagement, focus, and reading comprehension, though challenges such as distractions from personal devices were observed. Overall, ICT integration positively influenced teaching reading by enhancing interactivity, student motivation, vocabulary acquisition, and summarizing the story, demonstrating its potential in modern education. Keywords: ICT Integration; Teaching Reading; Vocational School; English Subject